Structuring overhead lines 35 – 750 kV in accordance with the concept Smart Grid - Cherkashyna, V. V. (GS publishing service Sherman Oaks, Los Angeles, 2021)
The presented article is devoted to the study of processes affecting the transmission of electricity. The study uses a discounted cost model for 35 - 750 kV overhead lines, which is improved by changing the analytical relationship of investment to wire cross-section. To analyze this model, a criterial method is used that allows decision making in relative units with incomplete initial information. In the course of research it was found that improving the structure of overhead lines 35– 750 kV by optimizing the parametric series of wires reduces the effect of network heterogeneity. The proposed direction has a number of features, in particular, it shows a consistent improvement in the structure of lines. In comparison with similar well-known approaches, the advantage of the proposed approach is that it allows to bring the energy facility for subsequent equipping with monitoring systems and control of the line operation parameters in accordance with the concept Smart Grid.
Keywords: monograph; discounted cost model; overhead lines; transmission of electricity; Smart Grid; electric networks; high-voltage